Conceptual Framework of Brand Image for Tourism Industry: Tourism Management and Advertisement as Moderators - Latif, Wasib B; Islam, Md Aminul; Rahman, Abdur; Mohamad, Mahadzirah; Kongsompong, Kritika (Journal of Tourism Management Research, 2016)
The conceptual framework of brand image for the tourism industry is a combination of antecedents and moderators that create differential effects on customer response to the tourism marketing of the brand. By constructing a conceptual framework of brand image for tourism industry will build a competitive advantage in the marketplace that will increase their overall image with long-term sustainability. Indeed, recent trends in modern tourism marketing have changed tremendously, and study of a conceptual framework of brand image for the tourism industry is increasingly becoming considerable to keep pace with this change. In this conceptual paper, we have summarized the literature on currently prevailing concepts and approaches on brand image for the tourism industry that will allow us to identify the conceptual framework of brand image, and therefore will facilitate the tourism industry to enhance their marketing efficiency and effectiveness.